2017
DOI: 10.3390/toxins9100294
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography-Mass Spectrometry for Metabolite Profiling of Japanese Black Cattle Naturally Contaminated with Zearalenone and Sterigmatocystin

Abstract: The objective of this study was to evaluate the metabolic profile of cattle fed with or without zearalenone (ZEN) and sterigmatocystin (STC)-contaminated diets using a gas chromatography-mass spectrometry metabolomics approach. Urinary samples were collected from individual animals (n = 6 per herd) from fattening female Japanese Black (JB) cattle herds (23 months old, 550–600 kg). Herd 1 had persistently high urinary ZEN and STC concentrations due to the presence of contaminated rice straw. Herd 2, the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Methylsuccinate, significantly increased in Group G2, has been previously related to ketotic conditions 38 , probably in relation to acyl-CoA dehydrogenase activity in the β-oxidation of fatty acids 39 . In accordance with the studies of 40 and 41 , high values of methylsuccinate in urine can be related to genetic disorders such as acyl-CoA dehydrogenase deficiencies.…”
Section: Discussionmentioning
confidence: 80%
“…Methylsuccinate, significantly increased in Group G2, has been previously related to ketotic conditions 38 , probably in relation to acyl-CoA dehydrogenase activity in the β-oxidation of fatty acids 39 . In accordance with the studies of 40 and 41 , high values of methylsuccinate in urine can be related to genetic disorders such as acyl-CoA dehydrogenase deficiencies.…”
Section: Discussionmentioning
confidence: 80%
“…Similar studies have shown that T-2 toxin disrupts the normal metabolic processing of energy and nutrient substrates, and changes the lipids and proteins in different organs and organelles. These metabolic processes involve pathways of molecular metabolism and modification, such as deacetylation, hydroxylation, and oxidation [ 20 , 52 ]. Therefore, mycotoxins are likely to affect various energy- and nutrient-directed metabolic processes in the body [ 2 , 7 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the increased lactate concentration in the rumen fluid after AFB1 exposure suggested shifts in both the cori and krebs cycles in response to changes in energy substrates [ 61 ]. A previous report indicated that biochemical parameters in the blood and urine can be used as reliable biomarkers of oxidative stress when different animals are fed diets contaminated with mycotoxins [ 2 , 20 , 72 ]. We also found significant differences in several serum oxidative biomarkers, such as SOD, T-AOC, and etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be routinely used to detect many nonpolar compounds such as fatty acids and sterols (Prenni et al, 2013;Tachibana, 2014). More important, GC-MSbased metabolomics analysis can provide an understanding of the metabolism of different dietary components such as dietary oils in farmed animals, including fish and crustaceans (Ma et al, 2017;Metzler-Zebeli, Ertl, Klein, & Zebeli, 2015;Saleem et al, 2012;Sun, Wang, Wang, Liu, & Liu, 2017;Sun et al, 2015;Toda et al, 2017).…”
mentioning
confidence: 99%